34 Eosinophilic myocarditis in patients on dobutamine therapy: an underappreciated and not uncommon phenomenon. (7th October 2015) - Barrett, M; Fabre, A; Tuohy, G; Ryan, N; Parlon, B; McCarthy, J; Nolke, L; McGuinness, J; Healy, D; Javadpour, H; Chugtai, Z; Mahon, N; et al.
Abstract : Background: The phenomenon of eosinophilic myocarditis in explanted hearts was first reported in a series in 1991. The phenomenon remains under-recognised and the incidence uncertain, current published estimates ranging widely from 7 to 22%. Aims: We sought to ascertain the incidence of eosinophilic myocarditis in our transplant centre and to assess if presence of an eosinophilic infiltrate was associated with dobutamine therapy prior to explant. Methods: 76 sequential heart transplant recipients over a 9 year period were included. Clinical records were examined to detail any exposure to inotropic support prior to transplantation as well as presence or absence of peripheral blood eosinophilia. Pathology reports of explanted hearts as well as any pre-transplant endomyocardial biopsies were reviewed and the presence or absence of eosinophils on histology was documented. Results: 28 patients (36.8%) of the group received dobutamine therapy prior to transplantation. Of these, 7 patients (25% of those receiving dobutamine, 9.2% of the total cohort) were found to have evidence of an eosinophilic infiltrate on myocardial histology (6 on explant, 1 on pre-transplant endomyocardia biopsy). All 7 patients had prolonged exposure to dobutamine prior to diagnosis of eosinophilic myocarditis. The duration of inotropic support ranged from 1 to 19 weeks; and the final maintenance dose of dobutamine ranged from 2.5 to 12.5 mcg/kg/min. One patient had a significant persistent peripheral blood eosinophilia for the duration of dobutamine therapy, 1.22 × 10 9 /L at peak (normal range 0.04 0.4 × 10 9 /L). A further 5 patients had short-lived (<3 days) minor elevations (<0.6 × 10 9 /L) in peripheral eosinophil count. Eosinophil count in these cases returned to normal without change in dobutamine dose or discontinuation. The patient with eosinophil infiltration on pre-transplant biopsy had dobutamine discontinued and histology of the explanted heart revealed complete resolution of the myocarditis. No eosinophilic infiltrates were identified in dobutamine-nave explants in the cohort, including 22 patients on prolonged therapy with intravenous milrinone. Conclusions: One in four patients exposed to prolonged dobutamine therapy in this series developed eosinophilic myocarditis. Additionally, complete resolution of eosinophilic myocarditis after discontinuation of dobutamine was detailed in vivo in one case. The clinical impact of this process in a heart failure cohort is not clearly understood. Specific attention may need to be paid to peripheral blood eosinophil count in patients requiring prolonged inotropic support.